Short‐term effects of povidone iodine and sodium fluoride therapy on plaque levels and microbiome diversity. (14th January 2016) - Reilly, C; Goettl, M; Steinmetz, M; Nikrad, J; Jones, RS
Abstract : Objectives: The objective of this study is to evaluate the effect of short‐term changes in the oral microbial ecology of dental plaque and plaque levels after topical treatment of a combination of 10% povidone iodine (PI) and 5% sodium fluoride varnish (FV). Materials and Methods: A single group design intervention study on 12 pediatric patients, who underwent two baseline plaques samplings before the intervention, were enrolled in the study. A modified mixed dentition Silness‐Löe plaque index score was used to assess plaque accumulation and microbial composition was assessed by amplicon sequencing analysis of the 16S rRNA V4 region. Results: Dental plaque accumulation ( P  = 0.0424) was reduced after 1 week using PI/FV application. This reduction was not observed between the two double‐baseline visits. 16S rRNA analysis showed that the single PI/FV therapy did not have dramatic shifts in the plaque microbiome community depicted by hierarchical cluster and principle component analysis. More subtle changes were found when analyzing the Shannon diversity index after the application of PI/FV vs two baselines prior to combination therapy. Conclusions: The bacteria within the dental biofilms showed resilience in maintaining the overall community diversity but reduced biofilm accumulation following PI/FV therapy. Repeated uses of PI/FV may augment plaque control during dental rehabilitation in children.